A generalized representation theorem for Harsanyi's ('impartial') observer - GRANT, Simon (Institutional Knowledge at Singapore Management University, 2012)
We provide an axiomatization of an additively separable social welfare function in the context of Harsanyi's impartial observer theorem. To do this, we reformulate Harsanyi's setting to make the lotteries over the identities the observer may assume independent of the social alternative.